Peran Linguistik Terapan dan Penerjemahan dalam Praktik Pembelajaran Bahasa Arab - Khairani, Putri Dian; Al Fajr, Rizka; Manalu, Samsia; Arifin, Jaenal; Susiawati, Iis (INCARE, International Journal of Educational Resources, 2025)
The research addresses the central question of how applied linguistics and translation contribute to enhancing the effectiveness of Arabic language learning in the modern era. The background of the study encompasses the dynamics of language development, the challenges of globalization, and educators’ limitations in adapting to technology and linguistic theories. This study aims to explain the interrelation between applied linguistics and translation, as well as their contribution to improving the quality of the teaching and learning process. Using a qualitative descriptive method through library research, the data were analyzed thematically and comparatively across theories in linguistics, psycholinguistics, sociolinguistics, pedagogy, and translation studies. The findings indicate that applied linguistics provides a scientific foundation that enables teachers to comprehensively understand the structure, meaning, social variation, and acquisition mechanisms of Arabic. Meanwhile, translation serves as a practical application that helps students develop vocabulary, comprehend grammatical structures, enhance analytical skills, and bridge the cultural context between Arabic and Indonesian. The integration of both fields has been shown to support mastery of the four language skills (listening, speaking, reading, writing) and to create more communicative and meaningful learning experiences. These conceptual findings underscore the urgency of integrating applied linguistics and translation in developing Arabic language teaching strategies that are adaptive to learners’ needs and global challenges.